The Influence of Green Intellectual Capital on Green Innovation Performance: The Mediating Role of Environmental Knowledge Sharing - Heri Widodo; Endra Wahyu Ningdiyah; Ruci Arizanda Rahayu; Muhammad Safdar (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2026)
This study aims to examine the effect of Green Intellectual Capital (GIC) on Green Innovation Performance (GIP), with Environmental Knowledge Sharing (EKS) as a mediating variable in food and beverage companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The increasing pressure for sustainability and environmentally friendly practices has encouraged firms to optimize their green knowledge resources to enhance innovation performance. This research adopts a quantitative approach using secondary data collected from annual and sustainability reports. The sample was determined through purposive sampling, resulting in 57 firm-year observations. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings indicate that GIC has a positive and significant effect on both GIP and EKS, suggesting that well-managed green intellectual resources contribute to improved innovation outcomes and facilitate knowledge exchange within organizations. In addition, EKS has a positive and significant effect on GIP and plays a mediating role in the relationship between GIC and GIP. This implies that the effectiveness of GIC in enhancing innovation performance is strengthened through the process of environmental knowledge sharing. This study contributes to the literature by integrating the Resource-Based View (RBV) and Knowledge-Based View (KBV) in explaining the mechanism through which intellectual capital drives green innovation. Practically, the results provide insights for companies to develop structured knowledge-sharing practices and optimize intellectual capital to support sustainable innovation strategies and long-term competitive advantage.